Pennies from heaven - Kaye, Nora; Ross, Herbert; Ross, Herbert; Martin, Steve 1945-; Peters, Bernadeth 1948-; Walken, Christopher 1943- (MGM/UA Home Video, 1981)
With drive and dexterity, Steve Martin triumphs as Arthur Parker, a Depression-era sheet-music salesman doomed forever to believe in the lyrics of the songs he sells. Though life steadily worsens for him and his schoolteacher mistress, he goes on believing it's still just a bowl of cherries-even when he's got nothing but the pits.